Simulation of the oxidative metabolization pattern of netupitant, an NK1 receptor antagonist, by electrochemistry coupled to mass spectrometry - Ruxandra Chira; Jens Fangmeyer; Ioan O. Neaga; Valentin Zaharia; Uwe Karst; Ede Bodoki; Radu Oprean (Elsevier, 2021)
Considering the frequent use of netupitant in polytherapy, the elucidation of its oxidative metabolization pattern is of major importance. However, there is a lack of published research on the redox behavior of this novel neurokinin-1 receptor antagonist. Therefore, this study was performed to simulate the intensive hepatic biotransformation of netupitant using an electrochemically driven method. Most of the known enzyme-mediated reactions occurring in the liver (i.e., N-dealkylation, hydroxylation, and N-oxidation) were successfully mimicked by the electrolytic cell using a boron-doped diamond working electrode. The products were separated by reversed-phase high-performance liquid chromatography and identified by high-resolution mass spectrometry. Aside from its ability to pinpoint formerly unknown metabolites that could be responsible for the known side effects of netupitant or connected with any new perspective concerning future therapeutic indications, this electrochemical process also represents a facile alternative for the synthesis of oxidation products for further in vitro and in vivo studies.